Correction to: Rabies Virus-Neutralizing Antibodies in Free-Ranging Invasive Wild Boars (Sus scrofa) from Brazil (Pathogens, (2024), 13, 4, (303), 10.3390/pathogens13040303) - Perin, Patricia Parreira [UNESP]; Turmina, Talita [UNESP]; Arias-Pacheco, Carmen Andrea [UNESP]; Gomes, Jonathan Silvestre [UNESP]; Andrade, Lívia de Oliveira [UNESP]; Zolla, Natália de Oliveira [UNESP]; Mendonça, Talita Oliveira [UNESP]; Oliveira, Wilson Junior [UNESP]; Fahl, Willian de Oliveira; Scheffer, Karin Correa; Cunha Neto, Rene dos Santos; Chierato, Maria Eduarda Rodrigues; et al. (MDPI, 2024)
There was an error in the original publication [1]. It was stated that two serum samples obtained from wild boars hunted in the municipality of Paraíso tested positive in the RFFIT, instead of one. A correction has been made to the first paragraph of Section 3, as follows: However, seven serum samples obtained from wild boars hunted in Monte Azul (four samples), Paraíso (one sample), Cajobi (one sample), and Colina (one sample). In the original publication [1], there was a mistake in Figure 2 as published. On the map, the municipality of Paraíso shows two positive samples instead of one. The corrected Figure 2 appears below. The authors state that the scientific conclusions are unaffected. This correction was approved by the Academic Editor. The original publication has also been updated.